Function of the N-terminal half of RepA in activation of Rts1 ori. - Terawaki, Y (1992)
The RepA protein of the Rts1 plasmid, consisting of 288 amino acids, is a trans-acting protein essential for replication. A mutant repA gene, repA delta C143, carrying a deletion that removed the 143 C-terminal amino acids of RepA, could transform, but at a low frequency, an Escherichia coli polA strain, JG112, when repA delta C143 was cloned into pBR322 with Rts1 ori in the natural configuration. The transformation was less efficient without the dyad DnaA box in the ori region, and no transformation occurred at 42 degrees C, characteristic of Rts1 replication. A fusion of the 3'-terminal half of repA of the P1 plasmid to repA delta C143 yielded a pBR322 chimeric plasmid that contained Rts1 ori through hybrid (Rts1-P1) repA. This plasmid was maintained much more stably in JG112 at 37 degrees C. At 42 degrees C, however, it was quite unstable. The overproduced hybrid RepA protein showed interference with mini-Rts1 replication in trans and also exhibited an autorepressor function, although both activities were decreased. These findings suggest that the N-terminal half of the RepA molecule of Rts1 is involved in the activation of the replication origin.